COMMUNICATION SKILLS TRAINING FOR HEALTH WORKERS TO IMPROVE SERVICES OF PUBLIC HEALTH CENTER AT SIDOARJO - Saptyasari, Andria; Titik Puji Rahayu; Ratih Puspa; Santi Isnaeni; Suko Widodo; Dina Septiani; Rani Sukma Ayu Suteja; Mytha Eliva Veritasia; Intan Fitranisa; Yuyun W. I. Surya; Angga Prawadika Aji; Irfan Wahyudi; Rachmah Ida; Yayan Sakti Suryandaru; Liestianingsih D (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The effective communication is crucial for providing good service at the Community Health Center (Puskesmas). One major issue that can lead to patient dissatisfaction is the communication skills of health workers. When these workers struggle to communicate well, patients may feel poorly served and find it hard to understand their health conditions and care instructions. To address this problem, the Communication Department of FISIP UNAIR organized a training called "Communication Skills Training for Health Workers to Improve Puskesmas Services at the Sidoarjo Regency." The aim of the training was to minimize communication errors between doctors and patients and enhance the community’s view of services at the Puskesmas. The training included various sessions for health workers. They had the chance to share their thoughts, understand patient backgrounds, and practice listening skills. They also learned how to use facial expressions, gestures, and polite language when communicating with patients through role-play exercises. The results of the training were positive. Participants could explain the material through role-play and improved their active listening skills. They managed their facial expressions, gestures, and voice tone better, and applied polite communication with patients from different backgrounds. A final survey showed a 25% increase in communication skills, improving from 55% to 80%. In summary, the community service team concluded that the training was well received and effectively implemented by participants at their health centers.